The best of Archie comics - Augustyn, Brian 1954-2022; Bolling, Bob 1928-; Doyle, Frank 1917-1996 (Archie Comic Publications, 2016)
"One of Archie's most popular graphic novels gets the deluxe treatment in this full-sized remastered hardcover edition collecting over 50 iconic favourite stories from across Archie's 75+ year history. The bestselling retrospective of this essential piece of Americana finally gets the treatment it's due in this keepsake bookshelf edition."--Provided by publisher
Keywords: Andrews, Archie / (Fictitious character) / Comic books, strips, etc; Lodge, Veronica / (Fictitious character) / Comic books, strips, etc; Jones, Jughead / (Fictitious character) / Comic books, strips, etc; Cooper, Betty / (Fictitious character) / Comic books, strips, etc; Mantle, Reggie (Fictitious character) / Comic books, strips, etc; High school students / Comic books, strips, etc; Teenagers / Comic books, strips, etc; Interpersonal relations / Comic books, strips, etc; Friendship / Comic books, strips, etc; Andrews, Archie / (Fictitious character); Jones, Jughead / (Fictitious character); Lodge, Veronica / (Fictitious character); Cooper, Betty / (Fictitious character); Friendship; High school students; Interpersonal relations; Mantle, Reggie (Fictitious character); Teenagers; Graphic novels; Coming-of-age comics; Comics (Graphic works); Comic